0517 Integrated Cognitive Behavioral Therapy (CBT) and Mindfulness Group Treatment Protocol for Insomnia and Chronic Pain. (27th May 2020) - Barwick, F; Poupore-King, H; You, D
Abstract: Introduction: Chronic pain and insomnia are highly comorbid, and CBT is a recommended treatment for both. CBT protocols that treat these conditions together, however, show improvements in sleep but not pain. As mindfulness, an acceptance-based approach, has been used successfully to treat chronic pain, integrating mindfulness into a combined CBT treatment protocol may help improve outcomes for chronic pain as well as insomnia. Methods: An integrated CBT/Mindfulness weekly 6-session group protocol for chronic pain and insomnia was developed and piloted. Treatment components included education about pain neuroscience as well as sleep and circadian biology, relaxation, time-based pacing, tracking 24-hour time in bed, sleep compression, stimulus control, cognitive reframing, and mindfulness. Pre-post measures evaluating insomnia symptoms, sleep hygiene, pain acceptance, pain catastrophizing, and unhelpful beliefs about sleep and pain were analyzed using frequency analyses and paired sample t-tests. Results: Two groups were completed for a total of 16 participants, 94% of whom attended at least 5 sessions. Average age was 56 years, 75% of the sample was female, 88% were White, 6% Asian, and 6% Latino. Post-treatment outcomes showed significant improvement in insomnia symptoms (ISI Mdiff =6.6, SDdiff =5.3, p=.01, ES=1.2), sleep hygiene (SHI Mdiff =3.8, SDdiff =4.6, p=.02, ES=.83), pain acceptance (CPAQ Mdiff =5.2, SDdiff =7.8, p=.03, ES=.67), pain catastrophizing (PCS Mdiff =5.1, SDdiff =7.5, p=.03, ES=.68), and unhelpful beliefs about sleep (DBAS Mdiff =31.4, SDdiff =21.2, p=.009, ES=1.5) and pain (PBAS Mdiff =11.6, SDdiff =10.7, p=.02, ES=1.1). Conclusion: An integrated CBT/Mindfulness group protocol for chronic pain and insomnia showed significant improvements in post-treatment sleep and pain measures. As previous combined CBT-only protocols showed pre-post improvement in sleep but not pain, the current study demonstrates that including mindfulness might improve outcomes for chronic pain. Future studies should compare CBT protocols for chronic pain and insomnia with and without mindfulness to determine the clinical benefits of including an acceptance-based component. Support: Poster presented as part of collaborative conversation with Skye Margolies, PhD, Department of Anesthesiology, University of North Carolina School of Medicine.